2018
DOI: 10.3390/joitmc4030039
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency Analysis of National R&D Planning for the Field of Precision Medicine in Korea

Abstract: Precision medicine has received a lot of attention in recent years and we have not yet found any research cases that apply Data Envelopment Analysis (DEA) to investment decision making in this area. The purpose of this study is to analyze the relative efficiency of candidate technology sectors in order to determine priorities for government investment in precision medicine. The results of the efficiency analysis can be used as an important reference for government policy makers to determine the amount of gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Various research has been conducted in the fields of ICT and R&D to measure relative efficiency. Beccheti et al [68] conducted research on investment, productivity, and efficiency regarding ICT, and Lee et al [69] performed efficiency analyses to obtain objective evidence concerning R&D investment. This suggests that decision makers provide clear justification and quickness for policymaking and resolve conflicts easily that may occur during the policy enforcement process, in addition to the need to consider the possibility of creating new industries or economic effects.…”
Section: Data Envelopement Analysismentioning
confidence: 99%
“…Various research has been conducted in the fields of ICT and R&D to measure relative efficiency. Beccheti et al [68] conducted research on investment, productivity, and efficiency regarding ICT, and Lee et al [69] performed efficiency analyses to obtain objective evidence concerning R&D investment. This suggests that decision makers provide clear justification and quickness for policymaking and resolve conflicts easily that may occur during the policy enforcement process, in addition to the need to consider the possibility of creating new industries or economic effects.…”
Section: Data Envelopement Analysismentioning
confidence: 99%
“…BangRae Lee, EunSoo Sohn, DongKyu Won, and WoonDong Yeo [9] analyzed the R&D investment efficiency of 23 industries in the field of precision medicine in South Korea. ey found that investment in these technologies can produce good benefits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jang [5] develops and applies a national R&D budget allocation model based on machine learning and optimization theory. Lee et al [6] use a data envelopment analysis (DEA) to analyze the relative efficiency of investment in the field of precision medicine. In addition, Kim et al [7] analyze the effect on investment performance of R&D actors, development levels, and periods, using technology transfer and diffusion as their performance measure for national R&D investment.…”
Section: Introductionmentioning
confidence: 99%